Implementation of article 5.3 of the world health organization framework convention on tobacco control: A subnational assessment - Praveen Kumar; Veena Kamath; Asha Kamath; Upendra Bhojani; Aastha Chugh; Shalini Bassi; Muralidhar M Kulkarni (Wolters Kluwer Medknow Publications, 2022)
Background: Article 5.3 of the World Health Organization's Framework Convention on Tobacco Control necessitates the governments to take measures to protect health policy from the commercial and other vested interests of the tobacco industry (TI). Considering the vast geographical area and diversity between states within India, it is necessary to evaluate the level of implementation of Article 5.3 at the sub-national level. Hence, this study was conducted to assess the implementation of Article 5.3 in the Karnataka state of southern India. Materials and Method: Southeast Asia Tobacco Control Alliance Tobacco Industry Interference index was adopted and used for the study. A desk review was conducted for 2018. Publicly available evidence of tobacco industry interference was scored based on its frequency, severity, and the government's response to it. Lower the score, effective the level of governance against the TI interference, which predicts well for the state. Results: The study demonstrates a score of 46 out of 95 in the implementation of Article 5.3 in Karnataka, which is lower when compared to the national score of 69 out of 100 for 2018. Corporate social responsibility, conflict of interest, and unnecessary interactions with TI are the major areas that need focus to comply with the provisions of Article 5.3. Conclusion: Overall, Karnataka needs to strengthen the implementation of Article 5.3 and develop a strategy in line with the global best practices. This assessment can help in identifying areas requiring enhanced vigilance to avoid industry interference.